Profanity on Malaysian Social Media: Implications on Brand Perception and Organisational Communication - Abdullah, Nur Nabilah; Ramdzan Ali, Al Amirul Eimer; Mohd Basari, Shahrul Nizam; Ramli, Mohd Safwan; Ayob, Nur Hidayah (Human Resource Management Academic Research Society (HRMARS), 2024)
The increasing prevalence of profanity on social media platforms raises concerns about its impact on communication and public perception. While studies on online incivility are growing, there is limited research on the use of harsh language on Twitter among Malaysians. Consequently, little is known about how profanity in the commentary sections of viral Twitter content affects interactions and perceptions among Malaysians. This study addresses the gap by examining the functions of profanity in Malaysian Twitter communications. The objectives are to analyse the communicative functions of profanity in tweets, assess its impact on brand perception among Malaysian users, and evaluate its implications for organisational communication strategies in Malaysia. Using content analysis, this research categorises and interprets the usage of profanity on Twitter. The finding reveals that Malaysians use harsh language for insult, emphasis, and informal expression, aligning with linguistic and social roles such as abusive, dysphemistic, idiomatic, and emphatic swearing. This research sheds light on how profanity influences brand perception and organisational communication, offering insights into its role in social media interactions. Understanding these patterns and communicative functions is crucial for enhancing our comprehension of profanity's role in social media interactions and for developing strategies to foster positive and respectful online communication.